2054. Trends in Incidence and Epidemiology of Methicillin-Resistant Staphylococcus aureus Bloodstream Infection, 2005–2020. (15th December 2022) - Biggs, Holly M; Jackson, Kelly A; Nadle, Joelle; Petit, Susan; Ray, Susan M; Lynfield, Ruth; Como-Sabetti, Kathryn; Bernu, Carmen; Dumyati, Ghinwa; Gellert, Anita; Tracy, Marissa; Schaffner, William; et al.
Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) is a serious antimicrobial resistance threat; prevention efforts have focused primarily on healthcare-associated MRSA infections. We assessed progress in MRSA bloodstream infection (BSI) prevention during 2005-2020. Methods: MRSA BSI data were from CDC Emerging Infections Program's active, population-based surveillance for invasive S. aureus in 17 counties in 6 states (sites). A case was defined as isolation of MRSA from a blood culture in a resident of the catchment area. Cases were considered hospital-onset (HO) if the culture was obtained > 3 days after hospitalization, healthcare-associated community-onset (HACO) if the culture was obtained in an outpatient setting or ≤ 3 days after hospitalization in a patient with ≥ 1 prior major healthcare exposures, or otherwise community-associated (CA). Annual incidence was calculated per 100, 000 census population for each epidemiologic classification. Results: MRSA BSI incidence decreased from 32.2 (per 100, 000 population) in 2005 to a nadir of 15.7 in 2016, then increased during 2017-2019 to 17.0 and decreased in 2020 to 16.4. (Figure 1). HACO comprised > 50% of all cases throughout 2005-2020 and mirrored the pattern of overall rates. HO rates decreased from 9.2 to 2.3 during 2005-2013 and fell below CA rates starting in 2012; rates were lowest during 2017-2019 (1.8-2.1) and increased in 2020 to 2.4. CA rates remained 3.0-4.6 throughout the surveillance period; during 2015-2019, rates increased from 3.0 to 4.0, then in 2020 decreased to 3.4. All sites saw decreases in overall MRSA BSI rates by > 50% during 2005-2020, and HACO rates in 2020 were at least 50% of total rates for each site. However, the relative proportion of CA and HO rates during 2020 varied by site (Figure 2), with CA MRSA BSI more than twice as common as HO MRSA BSI in two sites. Figure 1. Incidence rates of methicillin-resistant Staphylococcus aureus bloodstream infection, by epidemiologic classification, in 6 Emerging Infections Program sites, 2005–2020 Figure 2. Ratio of incidence (per 100, 000 population) of community-associated (CA) to hospital-onset (HO) methicillin-resistant Staphylococcus aureus bloodstream infection, in 6 Emerging Infections Program sites, 2020 Conclusion: MRSA BSI rates fell by more than half during the 15-year surveillance period, reflecting substantial declines in HACO and HO cases; however, the recent plateau suggests a need for additional preventive measures that restore previous progress. Increased focus on CA MRSA BSI prevention may be needed in some areas depending on local epidemiology. Disclosures: Ghinwa Dumyati, MD, Pfizer: Grant/Research Support William Schaffner, MD, VBI Vaccines: Advisor/Consultant.